A minimal timescale for the continuum in 4U 1608-52 and Aql X-1. Issue 1 (14th January 2021) - Mohamed, K; Sonbas, E; Dhuga, K S; Göğüş, E; Tuncer, A; Abd Allah, N N; Ibrahim, A
ABSTRACT: Similar to black hole X-ray binary transients, hysteresis-like state transitions are also seen in some neutron-star X-ray binaries. Using a method based on wavelets and light curves constructed from archival Rossi X-ray Timing Explorer observations, we extract a minimal timescale over the complete range of transitions for 4U 1608-52 during the 2002 and 2007 outbursts and the 1999 and 2000 outbursts for Aql X-1. We present evidence for a strong positive correlation between this minimal timescale and a similar timescale extracted from the corresponding power spectra of these sources.